The Influence of Working Capital Turnover and Net Profit Margin (NPM) on Return on Asset (ROA) at PT Indofood Sukses Makmur Tbk (Case Study Listed on the Indonesia Stock Exchange for the 2015-2022 Period) - Siti Rokayah; Asep Achmad Rifa’I (Formosa Journal of Social Sciences (FJSS), 2024)
Researchers aim to determine the influence of Working Capital Turnover and NPM on Return On Assets. The object of this research was carried out at PT Indofood Sukses Makmur Tbk, with this type of research using a quantitative approach with an associative descriptive approach. Secondary data was collected from financial reports for 8 years, from 2015 to 2022, divided into 3 months. For data research, documentation techniques are used. The 2015–2022 financial reports are the subject of this research. A purposive sampling method was used. Next, the data for analysis is used through the classic assumption test, which consists of four tests: heteroscedasticity, normality, multicollinearity, and autocorrelation as a correlation study; analysis of the coefficient of determination; linear regression; and simultaneous and partial hypothesis testing. The research results show that working capital turnover partially and significantly has a negative effect on Return On Assets in the 2015–2022 period of PT Indofoood Sukses Makmur Tbk, while net profit margin has no effect on Return On Assets. On the other hand, working capital turnover and net profit margin simultaneously influence Return On Assets. Influential assets